A critical review on nickel sulfide-based electrode materials for supercapacitors - Wang, Yu-Ting; He, Xiong-Fei; He, Guang-Yuan; Meng, Chao; Chen, Xue-Min; Li, Fa-Tang; Zhou, Yue (Critical reviews in solid state and materials sciences, 2023)
Supercapacitors (SCs) are currently numbered among the most outstanding energy storage and supply devices due to their high power density, durable cycle life, and wide operating temperature range. However, the wide application of SCs is still subject to the low energy density, which drives researchers to extensively look for high-performance electrode materials. In recent years, nickel sulfide-based materials have been widely studied as promising electrode materials for SCs due to their superior theoretical specific capacity, high redox activity, and rapid electric conduction, but the inferior active material utilization efficiency and poor reaction kinetics limit their practical demand in SCs. In this review, we briefly introduced the energy storage mechanism of nickel sulfide electrode materials used in supercapacitors and then launched an overview of improving performance. A particular emphasis is on the modification strategies to accelerate the electron conduction and mass transfer process through carbon recombination, metal heteroatom doping, interfacial electric field construction, exposure of edge active sites and large specific surface area, and building of ion diffusion channels. Finally, we discuss the research orientation of nickel sulfide-based electrode materials.